Insect seedling herbivory is influenced by multiple factors, but the plant apparency theory is more supported than other hypotheses – A case study in a subtropical forest - Baozhu Yuan; Bo Wang (Forest Ecosystems)
Insect herbivory is ubiquitous in various ecosystems, and directly influences the growth and survival of individual plants, especially during their vulnerable early life stages like the seedling phase. This, in turn, exerts a significant influence on forest community diversity and structure, as well as ecosystem function and stability. Notable variation in herbivory has been detected both among and within plant species. For decades, many hypotheses have been proposed to explain such variations, including both biotic and abiotic variables. However, most studies have considered only one or several of these hypotheses by focusing on a few potential variables, and their results were usually inconsistent; thus, the factors driving herbivory remain unclear. In this study, we examined leaf herbivory by insects of woody species seedlings in a subtropical forest in southwestern China over two seasons. In total, 24 potential variables that represented abiotic resource availability, characters of individual seedlings, conspecific and heterospecific species, and the whole seedling community were selected to test several commonly discussed alternative herbivory hypotheses. Overall, our findings showed that the plant apparency hypothesis was more supported than the other hypotheses in explaining insect seedling herbivory. Our results further indicated that the mechanisms and causes of insect herbivory are complex, multifactorial, species-specific and vary with seasons, indicating that there may be no uniform rules in explaining herbivory for all seedlings. Consequently, such complexity may play an important role in promoting species coexistence and biodiversity maintenance in seedling communities, which may further translate into the following generation of saplings or even adult communities. Changes in the community of insect herbivores and/or variables influencing insect herbivory, may disrupt stability of the original seedling community, thus affecting the regeneration and development of the entire forest community. Therefore, we suggest that issues related to insect herbivory should be considered when developing forest management and conservation.